Density difference between perilymph and endolymph: A new hypothesis for light cupula phenomenon. (February 2019) - Kim, Chang-Hee; Pham, Ngoc Chien
Abstract: Light cupula is an emerging concept accounting for positional nystagmus. It can be diagnosed when persistent geotropic direction-changing positional nystagmus (PG DCPN) is observed in a head-roll test. Although hypotheses explaining light cupula phenomenon such as "light debris", "lighter cupula", and "heavier endolymph" have been proposed, the mechanism underlying light cupula has not been clearly elucidated yet. In the present study, we proposed a new hypothesis accounting for light cupula, i.e., density difference between perilymph and endolymph could elicit characteristic PG DCPN in a head-roll test. We also discussed the mechanism how membranous canal containing endolymph became buoyant within the perilymphatic space under constant influence of gravity when the density of perilymph was higher than that of endolymph.